An Analysis of the Language Styles Used in Discovery Kartika Plaza Hotel Advertisements - Kadek Ayu Ira Amelia Dewi; I Ketut Armawan; Ni Putu Era Marsakawati (Association of Islamic Education Managers (Permapendis) Indonesia, North Sumatra Province, 2025)
This research aims to analyze the language style used and the message conveyed in Discovery Kartika Plaza Hotel Advertisements. The research design used in this study is descriptive qualitative. The researcher, table, and notebook are instruments used in this research. Based on the findings and discussion, there are 7 types of language styles from 20 data points found. The language styles are 1) Hyperbole, 2) Metaphor, 3) Alliteration, 4) Personification, 5) Metonymy, 6) Prolepsis, 7) Synecdoche. Hyperbole is one of the most frequently used language styles in hotel advertisements, with a frequency of occurrence of 25% of all language styles analyzed. The message conveyed to the reader is that the language style used in Discovery Kartika Plaza Hotel advertisements is carefully designed to persuade and attract potential guests by evoking emotions, creating a sense of luxury or comfort, and highlighting unique experiences.